Effect of chronic traffic noise on behavior and physiology of plateau pikas (Ochotona curzoniae) - Qu, Jiapeng; Wang, Yun; Kong, Yaping; Zhu, Hongjuan; Yu, Yibo; Zhong, Liang (Frontiers in Ecology and Evolution, 2022)
During the last two decades, numerous studies have shown the effects of traffic noise on animal vocal communication. However, studies on the influences of traffic noise on wildlife behavior and physiology are scarce. In the present study, we experimentally manipulated the traffic noise exposure of plateau pika, a native small mammal widely distributed in the alpine meadow of Qinghai-Tibet Plateau, to explore the effects of traffic noise exposure on its behavior and physiology. We showed that noise exposure increased the pika’s exploration and cortisol concentration (CORT) but decreased the resting metabolic rate (RMR). In addition, the relationships between RMR and exploration or CORT appeared under traffic noise treatment. This study suggests that traffic noise plays a large role in the behavior and physiology of plateau pikas and may have a long-term negative effect on the fitness of rodent populations. Generalizing these non-lethal effects to different taxa is crucial for the conservation and management of biodiversity in this increasingly noisy world.